Phosphorylation of Glycine Derivatives via Copper(I)‐Catalyzed Csp3−H Bond Functionalization. Issue 15 (2nd August 2016) - Zhi, Huizhen; Ung, Sosthene Pierre‐Marie; Liu, Yun; Zhao, Liang; Li, Chao‐Jun
Abstract: A simple and efficient one‐pot approach has been developed for a copper‐catalyzed phosphorylation of glycine derivatives under air and at room temperature. The present cross‐dehydrogenative coupling allows various methoxyphenyl‐protected glycine derivatives to be phosphorylated using diverse alkyl and aryl phosphites through an oxidative coupling between C sp 3 −H and P−H bonds catalyzed by copper iodide. This method provides a new synthetic tool to obtain biologically active α‐aminophosphonates. Abstract :